Two Contrasting Demographic Processes Shape the Divergence and Evolution of the Widespread Arid Zone Specialist, Petrogale lateralis - Sally Potter; Craig Moritz; Kym Ottewell; Emily Roycroft; Anna J. MacDonald; Margaret Byrne; Steven J. B. Cooper; David J. Pearson; Mark D. B. Eldridge (Molecular Ecology, 2026)
Organisms living in arid environments are predicted to be at increased risk of extinction under climatic and anthropogenic change. Response to past climate change can provide some insights into these risks; however, our understanding of the diversification and evolutionary history of many arid‐adapted species is still limited, particularly in Australia. Here, we evaluate the demographic and evolutionary history of a widespread Australian marsupial, the black‐footed rock‐wallaby ( Petrogale lateralis ), with a highly fragmented contemporary distribution across Australia's arid biome and offshore islands. Combining genomic data from historical and modern samples, we evaluate the divergence history of the five P. lateralis subspecies. Our results show that the species has experienced a Pleistocene‐age demographic expansion across the Australian arid biome, with subsequent geographic fragmentation of populations and subspecies. We find negligible gene flow between most extant populations/subspecies, yet low divergence between populations of P. l. lateralis and currently recognised subspecies. Individuals on islands have extremely low genetic diversity and high inbreeding coefficients, in contrast to naturally fragmented mainland populations, suggesting a stronger bottleneck experienced on islands. Our results indicate connectivity of populations within the past ~160–640 kya despite their current disjunct distributions, providing important context for conservation management and potential genetic rescue. However, given the large ecological gradient and chromosomal variation within this species, assessment of ecological differences and risks of outbreeding depression will be important before decisions to mix across geographically distant populations and/or subspecies. This study demonstrates how museum genomics improves our ability to resolve complex evolutionary histories and guide conservation.